Quality and antioxidant potential of ‘BRS Magna’ grapes harvested in the first half of the year under different training systems and rootstocks in a tropical region - Ferreira,Talita de Oliveira (2019)
ABSTRACT The Submedium São Francisco Valley is renowned for its particular conditions for cultivating grapes for different uses. The production of grapes for juice is relatively recent, and thus, knowledge is still limited on components of the production system. The aim of this study was to characterize the quality and antioxidant activity of ‘BRS Magna’ grapes in irrigated crops of the Submedium São Francisco River Valley under the influence of training systems and rootstocks, in production cycles of the first half of the year. The experiment was conducted in the Experimental Field of Bebedouro/Embrapa Semiárido, in Petrolina, Pernambuco, Brazil. The following were studied: overhead trellis, lyre, and vertical shoot positioning (VSP) systems and rootstocks ‘IAC 572’ and ‘IAC 766’, in the production cycles corresponding to the first halves of 2017 and 2018. Experimental design was in randomized blocks, with sub-subplots through time and four replicates. Overall, responses depended on training systems, rootstocks, and production cycles, which determined specific traits of the grapes. Production in the first half of 2018 was characterized by high anthocyanin contents, high total extractable polyphenols, and higher antioxidant activity, and responses were differentiated according to training system and rootstock. Plants trained to overhead trellis and grafted on ‘IAC 572’ had higher accumulation of total extractable polyphenols and antioxidant activity in berries. Plants trained to VSP had increased sugar, yellow flavonoid, and anthocyanin contents in berries while lyre training system led to higher bunch mass.